2020
DOI: 10.21608/jhiph.2020.70678
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of National Breast Cancer Screening Programs in Developing Countries, with Reference to the Recent Egyptian Initiative

Abstract: Breast cancer was the second most common cancer in the world and the most common cancer in women both in developed and less developed world. It ranked the fifth cause of death from all cancers and caused the greatest number of cancer related deaths among women in 2018. A variety of factors have been shown to impact an individual's risk of developing breast cancer and its ultimate prognosis. Screening for breast cancer will help to reduce mortality, to confer lifetime protection, and to protect those with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the meantime, there was no discernible difference with regard to Alu115 (p=0.497). Table (3) and diagram (2).…”
Section: And Alu 247 Were Higher In Bc Cases Than Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, there was no discernible difference with regard to Alu115 (p=0.497). Table (3) and diagram (2).…”
Section: And Alu 247 Were Higher In Bc Cases Than Healthy Controlsmentioning
confidence: 99%
“…Its burden has been rising in many countries and in 2040, more than three million new cases and one million deaths were expected (1) . In Egypt, BC accounts for 35.1% of cases among females and reports stated that it carries bad prognosis with 29% mortality rate (2) . Many studies have found increased concentrations of cfDNA and its integrity in various types of malignancy including BC (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…This is why it is important to highlight the importance of screening for HCC for all individuals with SVR for cirrhotic features for life. Increasing public awareness of the importance of the screening is warranted just as in the national screening campaign for breast cancer in Egypt 2020[ 178 ].…”
Section: Hcc Screening After Hcv Treatment With Daasmentioning
confidence: 99%
“…Major screening programs in Egypt, like the National Initiative of 100 Million Healthy Individuals and Breast Cancer 2020 have produced high success rates[ 178 ]. Now it is time for proper guidance and screening programs for HCC in Egypt.…”
Section: Hcc Screening After Hcv Treatment With Daasmentioning
confidence: 99%
“…Breast cancer initiative; a global campaign to reduce disparities in breast cancer outcomes and improve access to breast health care for 2.5 million women by 2025 (UICC global cancer control 2020). The launching of the first Egyptian national screening program "Women Health Outreach Program" (WHOP) was announced on October 30th 2007 (Wahdan, 2020).…”
Section: Introductionmentioning
confidence: 99%